The effect of domestic and public investment on economic growth in Somalia - Abdullahi Mohamud, Yasmin; Ma'rof, Aini Azeqa; Mohamed, Abdullahi Mohamud; Mohamed Ali, Abdullahi (Human Resource Management Academic Research Society, 2023)
Government expenditures possess the potential to exert either a favorable or detrimental influence on an economy. Augmentations in public investment yield augmented yields, enhancing the output and employment status of any nation and propelling economic expansion. The study conducts an in-depth investigation into the intricate relationship between government spending, public investment, and their impact on economic growth. It offers a nuanced understanding of this complex interplay by drawing on economic theories, empirical studies, and real-world examples. The study employs robust econometric methods, specifically the Ordinary Least Squares (OLS) regression, to investigate the impact of public investment and domestic investment on GDP growth. The results reveal a strong and positive relationship between both public investment and domestic investment with economic growth. Specifically, a one percent increase in domestic investment correlates with a substantial 53.1 percent increase in GDP, emphasizing the significance of private sector investments. Similarly, a one percent increase in public investment results in a notable 23.3 percent GDP increase, highlighting the role of government-led initiatives, particularly infrastructure projects, in promoting economic growth. These findings validate the importance of a balanced approach that leverages both public and private investments for sustainable economic growth. The study underscores the importance of balancing public and private investments for economic growth while emphasizing the need for tailored policies that consider specific contextual factors in emerging economies like Somalia.